Mechanical performance of fibre reinforced concrete : the role of fibre distribution and orientation - Abrishambaf, Amin (2014)
Adding fibres to concrete provides several advantages, especially in terms of controlling the crack opening width after the cracking initiation of the composite. However, distribution and orientation of the fibres toward the crack plane are significantly important in order to provide the maximum benefit for controlling crack width. Therefore, in this study, the effect of the fibre distribution and orientation on the tensile behaviour of the steel fibre reinforced self-compacting concrete (SFRSCC) specimens is investigated. For this purpose, cores that are extracted from distinct locations of a panel will be subjected to indirect (splitting) and direct tensile tests. By modeling the splitting tensile test under the finite element framework and by performing an Inverse Analysis (IA), the achieved stress-crack opening relationship (σ-w) is compared with the one obtained directly from the experimental curve obtained in the direct tensile tests.